2009
DOI: 10.1603/033.046.0114
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of the Aqueous Extract ofAzadirachta indica(Neem) Wood Chippings onAnopheles gambiaes.s. (Diptera: Culicidae) Mosquitoes

Abstract: Azadirachta indica A. Juss (the neem tree), a source of limonoid insect growth regulatory (IGRs), grows well in many places in sub-Saharan Africa. We explored the potential of neem wood and bark chippings in malaria vector control by evaluating their aqueous extracts as a larvicide and growth disruptor of Anopheles gambiae s.s. (Diptera: Culicidae) under laboratory conditions. Immature stages of the mosquito were tested using WHO guidelines. Fifty percent inhibition of adult emergence (IE50) of all larval inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 28 publications
2
30
0
1
Order By: Relevance
“…These actions are based on multiactions against insects: toxicity, antimitotic effects, antifeedant activity, growth regulation, fecundity suppression, sterilization, oviposition repellency, including harmful effects on endocrinien system and damages of the cuticle of larvae preventing them from moulting . Also aqueous extracts of neem wood and bark chippings showed larvicidal activity against A. gambiae (Howard, 2009); in this extracts HPLC analysis showed the presence of a series of constituents of varying polarity, including nimbin and salannin, whereas AzA was not detected. Structure complexity of Az and other bioactive neem constituents precludes any large-scale chemical synthesis by the extremely high cost.…”
Section: Using Neem Treementioning
confidence: 86%
See 1 more Smart Citation
“…These actions are based on multiactions against insects: toxicity, antimitotic effects, antifeedant activity, growth regulation, fecundity suppression, sterilization, oviposition repellency, including harmful effects on endocrinien system and damages of the cuticle of larvae preventing them from moulting . Also aqueous extracts of neem wood and bark chippings showed larvicidal activity against A. gambiae (Howard, 2009); in this extracts HPLC analysis showed the presence of a series of constituents of varying polarity, including nimbin and salannin, whereas AzA was not detected. Structure complexity of Az and other bioactive neem constituents precludes any large-scale chemical synthesis by the extremely high cost.…”
Section: Using Neem Treementioning
confidence: 86%
“…General cautions must be taken for the possible presence of aflatoxins, usually present in case of bad storage, as in other botanical raw materials. The results showed that neem products could act primarily as larvicides (Zebitz, 1986(Zebitz, , 1987Naqvi et al, 1991;Rao et al, 1992Rao et al, , 1995Amorose, 1995;Wandscheer et al, 2004;Okumu et al, 2007, Howard et al, 2009. Organic solvent extracts and oils from neem and Melia azedrach have displayed several bioactivities against insects governing chemical maturation of molt hormones, chitin biosynthesis and field deterrence.…”
Section: Using Neem Treementioning
confidence: 99%
“…Hence, flavonoids and polyphenolic compounds in Siamese neem tree, and its potent antioxidant activity might play a role to inhibit PbANKA growth in vivo. In addition, it has been described that azadirachtin and nimbin, most active compounds in Siamese neem tree might also play a role in antimalarial activity [25][26][27]. Interestingly, oxidative damage in order to inhibit malaria parasite of artemisinin has been reported, and might related to antimalarial property of Siamese neem tree extract.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium anacardate from cashew nut shell liquid was evaluated against A. aegypti eggs, larvae and pupae and found to be highly toxic to all life stages, although the dose required to kill the pupae was much higher than that needed to kill larvae (Farias, et al 2009). This is not uncommon for botanical products (Howard, et al 2009). The authors also tested the effect against mice.…”
Section: Plantsmentioning
confidence: 91%
“…In the latter bracket, 14 Mexican medicinal plants were tested and a range of toxicity was found, with some being highly toxic and others showing very little larvicidal effect (Reyes-Villanueva, et al 2008). The neem tree (Azadirachta indica) is a well known medicinal plant that has been widely tested against mosquitoes (Howard, et al 2009;Fallatah and Khater, 2010). When tested against dengue vectors neem was found to be effective at relatively low doses (Wandscheer, et al 2004) but oviposition was inhibited (Coria, et al 2008).…”
Section: Plantsmentioning
confidence: 99%